2019
DOI: 10.1097/aud.0000000000000594
|View full text |Cite
|
Sign up to set email alerts
|

Tinnitus Severity Is Related to the Sound Exposure of Symphony Orchestra Musicians Independently of Hearing Impairment

Abstract: Musicians frequently report tinnitus. Any tinnitus and severe tinnitus are significantly associated with the cumulative lifetime sound exposure, which was shown to be the most important factor not only for the prevalence but also for the severity of tinnitus-even in musicians without hearing loss. High-frequency hearing thresholds and tinnitus severity were correlated only if the cumulative lifetime sound exposure was excluded from the analyses.This is an open-access article distributed under the terms of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 46 publications
1
7
0
4
Order By: Relevance
“…Even if loud classical music poses a lower risk of NIHL than a similar dose of heavy metal music or industrial noise, the negative result of Karlsson et al [ 123 ] has been overturned by many subsequent studies [ 118 , 120 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 ]. For example, Royster et al [ 118 ] found that Chicago Symphony Orchestra musicians were exposed at just above the NIOSH REL during their 15 h of weekly rehearsals and performances (not counting solitary practice).…”
Section: Loud Music and Leisure Noise Is A Common Cause Of Permanent Hearing Loss Tinnitus And Hyperacusismentioning
confidence: 99%
“…Even if loud classical music poses a lower risk of NIHL than a similar dose of heavy metal music or industrial noise, the negative result of Karlsson et al [ 123 ] has been overturned by many subsequent studies [ 118 , 120 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 ]. For example, Royster et al [ 118 ] found that Chicago Symphony Orchestra musicians were exposed at just above the NIOSH REL during their 15 h of weekly rehearsals and performances (not counting solitary practice).…”
Section: Loud Music and Leisure Noise Is A Common Cause Of Permanent Hearing Loss Tinnitus And Hyperacusismentioning
confidence: 99%
“…Understandably, poor indoor environmental quality adversely affects the performance and health of building users (Bughio et al, 2020). Research also showed that poor acoustic performance including music, can have a negative impact on health, behaviour and cognitive function (Alves et al, 2015;Challe, 2015;Emenike & Sampson, 2017;Hodgson, 2008;Schmidt et al, 2019;Murphy & King, 2014;Nurzyński, 2005;Nyoni, 2015;Oloruntoba et al, 2012;Silva, 2015; The Department of Health, 2018; Treasure, 2012; WHO, 2011, 2018), due to lack of awareness of how poor acoustic quality affects us and to total lack of understanding of acoustic as an integral part of either aesthetics or functionality of a building (Wilson, 2017). Okoye et al (2020b) even found that that undirected loud music sounds severely affect the sustainability performance of buildings socially, environmentally, economically and technically.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Tinnitus can be debilitating and have a great impact on musicians private and professional lives [25]. A study by Schmidt et al (2019) noted that the presence of tinnitus, whilst not consistently identified as attributed to noise-induced hearing loss (NIHL) may be related to noise exposure, meaning musicians can be considered a high-risk group and that the percept has potential to interfere with professional functioning, as well as outside of professional work. Schmidt et al (2019) used a questionnaire which included two questions relating to whether musicians found tinnitus to be "a problem" during and/or outside of orchestral life.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Schmidt et al (2019) noted that the presence of tinnitus, whilst not consistently identified as attributed to noise-induced hearing loss (NIHL) may be related to noise exposure, meaning musicians can be considered a high-risk group and that the percept has potential to interfere with professional functioning, as well as outside of professional work. Schmidt et al (2019) used a questionnaire which included two questions relating to whether musicians found tinnitus to be "a problem" during and/or outside of orchestral life. Although the breadth of the study did not explore the specific ways in which tinnitus may impact the professional and non-professional lives of musicians, it highlighted some interesting findings.…”
Section: Introductionmentioning
confidence: 99%